Belize : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2022)
The COVID-19 pandemic had a severe impact on Belize in 2020, leading to a 16.7 percent contraction in real GDP and a rise in public debt to an unsustainable level of 133 percent of GDP. To address this situation, the government presented a medium-term plan to lower public debt to 85 percent of GDP in 2025 and 70 percent in 2030 by implementing fiscal consolidation, structural reforms, and debt restructuring. Significant progress towards restoring debt sustainability was made in 2021.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Belize